2014
DOI: 10.1016/j.parint.2013.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Plasmodium immunobiology in the liver, brain, and lung

Abstract: Plasmodium falciparum malaria is responsible for the deaths of over half a million African children annually. Until a decade ago, dynamic analysis of the malaria parasite was limited to in vitro systems with the typical limitations associated with 2D monocultures or entirely artificial surfaces. Due to extremely low parasite densities, the liver was considered a black box in terms of Plasmodium sporozoite invasion, liver stage development, and merozoite release into the blood. Further, nothing was known about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 265 publications
2
35
0
1
Order By: Relevance
“…Another much worthy improvement of the technique involves objectives [9,10,77], or graded-index (GRIN) lenses [78,79], with extremely slim diameter tips (about 1 mm) that require a much tinier thoracotomy. The reduced optical efficiency of these lenses in terms of field of view and numerical aperture is counterbalanced by a much reduced invasiveness.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another much worthy improvement of the technique involves objectives [9,10,77], or graded-index (GRIN) lenses [78,79], with extremely slim diameter tips (about 1 mm) that require a much tinier thoracotomy. The reduced optical efficiency of these lenses in terms of field of view and numerical aperture is counterbalanced by a much reduced invasiveness.…”
Section: Imagingmentioning
confidence: 99%
“…The second section of this review describes these very techniques, beginning with pioneers such as Malpighi who intellectually filtered his unstable observation before drawing the resulting image, to computerized post-processing strategies based on frame registration of oversampled acquisition through mechanically-stabilized organ. These latter techniques have recently opened a new exciting window upon the dynamic study of the pulmonary immune system [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Different from that observed in humans, during ECM, the adhesion of leukocytes and lymphocytes in the brain vasculature is well described [71,74,77]. In fact, monocytes, CD4 + T cells, CD8 + T cells and platelets adhere in brain post capillary venules but do not transmigrate to the brain tissue of P. berghei infected mice, supporting the idea that the brain disorder is due to leukocyte induced-endothelial dysfunction.…”
Section: Inflammatory Components In the Development Of Cerebral Malariamentioning
confidence: 73%
“…Recent evidence showed that Plasmodium berghei-ANKA infected RBCs adhere to brain microvascular endothelial cells in a VCAM-1-dependent manner [73]. In addition, another study suggests transient contact between infected RBCs and the endothelium [74]. The expression of Pf-erythrocyte membrane protein (EMP)s and their ability to adhere to host adhesion molecules depends on the expression of structural proteins, such as knob-associated histidine-rich protein (KAHRP), that allow the formation of knobs on erythrocyte membranes [75].…”
Section: Inflammatory Components In the Development Of Cerebral Malariamentioning
confidence: 98%
“…Incidence of clinical signs of cerebral malaria (CM) that involves neurological syndromes such as ataxia, paralysis, deviation of the head, convulsions, decrease in body temperature, loss of vascular cell integrity, tissue edema, hemorrhages in the brain of mice, and congestion of micro-vessels with parasitized erythrocytes and/or mononuclear cells was assessed [18,19].…”
Section: Assessment Of Cerebral Syndromesmentioning
confidence: 99%